Pengaruh Pengeluaran Pemerintah, Pembangunan Manusia, dan Tenaga Kerja Terhadap Ketimpangan Pendapatan Indonesia - Devita Fatma Wulandari; Farida Rahmawati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study is intended to provide an explanation regarding the effects resulting from government expenditure, labor, and human development on income inequality in Indonesia. Documentation study technique was used in the data collection process. While the use of this research data by using the type of time series taken in 2004-2020, so that the period of this research is 17 years. The method used in this quantitative descriptive research is through multiple linear regression analysis with STATA 13 analysis tool. The findings of the study show that the government expenditure variable, labor variable, and human development variable simultaneously (F-test) have a significant influence on the income inequality variable. Meanwhile, the results of the t-test partially indicate that government expenditure has a significant and positive effect if it is associated on income inequality. The next variable, namely the workforce, indicates that the relationship with income inequality is positive but the effect is not significant. Meanwhile, another significant influence is found in the human development variable and the relationship is negative when analyzed on the income inequality variable